Prevalence and public health significance of rabies virus in bats in the North Region of Cameroon. - Isaac Dah; Rodrigue Simonet Poueme Namegni; Mohamed Moctar Mouiche Mouliom; Simon Dickmu Jumbo; Ranyl Nguena Guefack Noumedem; Isabelle Conclois; Liegeois Florian; Laurent God-Yang; Jean Marc Kameni Feussom; Abel Wade; Dorothée Missé; Julius Awah-Ndukum (Public Library of Science (PLoS), 2023)
Background Rabies is a zoonotic disease of all warm-blooded animals including humans. There is a paucity of data on the status of rabies in wild animals in Cameroon and the disease is endemic in the country with dogs being the main source of transmission. Bat habitats are widespread in Cameroon, but there is limited information on the prevalence of rabies in bats, and their role of as potential reservoirs of rabies virus. Methods A cross sectional study was carried out to estimate the prevalence and to assess risk factors of rabies virus in bats in the North Region of Cameroon. A total of 212 bats belonging to three families (Pteropodidae, Vespertilionidae and Molossidae) and 5 species were sampled in 7 localities in the North Region of Cameroon and were tested for rabies virus antigen using direct Immunofluorescence Test (IFA). Results Overall, 26.9% (57/212) of the bats collected showed an IFA positive reaction. The prevalence was significantly higher (P<0.05) in adult bats (33.3% (36/108)) compared to young individuals (20.2%; 21/104). The main risk factors identified in the study for human exposure to bats were gender (Male), religion (Christianity), localities (Babla and Lagdo), the practice of bat hunting, bat consumption, unawareness of bat rabies and cohabitation with bats in close proximity. Conclusion The study revealed the first evidence of Lyssavirus in bats in Cameroon. This finding showed that bat rabies are real and represents a potential public health concern in communities with bat habitats in the North Region of Cameroon. Enhancing the level of public awareness and health education on the potential of bats as reservoirs of Lyssavirus in Cameroon as well as the integration of the "One Health" approach for effective management of animal and human rabies should be emphasized.